UJI MUTU FISIK TEH HERBAL DAUN BAMBU KUNING (Bambusa vulgaris Schrad) - NURUL HIDAYAH BASE; Sitti Rachmawati; ARIEF N NOENA, RAYMOND (Akademi Farmasi Yamasi Makassar, 2023)
Yellow Bamboo Leaf is a plant that is known to have anti-oxidant, anti-inflammatory, anti-diabetic and anti-ulcer properties. Phytochemical screening in previous studies, ethanol extract of yellow bamboo leaves contains flavonoids, polyphenols, triterpenoids and saponins. The purpose of this study was to make herbal preparations and test the physical quality of the herbal preparations of yellow bamboo leaves. This research method is an experimental laboratory by making herbal preparations of yellow bamboo leaves with a concentration of 2.5%, then tested for physical quality. The quality requirements of the results showed that the yellow bamboo leaf herbal tea met the requirements of good physical quality, including: the state of the steeping water test including the color, smell and taste showed